Improving Activities and Learning Outcomes with The SENANG Model in Primary Students - Fransiska, Nola; Agusta, Akhmad Riandy; Rafianti, Wahdah Refia (Journal Of Foreign Language Learning and Teaching, 2024)
This research aims to describe teachers' activities and analyze students' activities and learning outcomes. The type of research used was Classroom Action Research (PTK) which was carried out in 3 meetings. The subjects of this research were class V students at SDN Kuin Cerucuk 5. The type of data used in this research was qualitative and quantitative. The results of the research show that teacher activity received a score of 30 with the criteria "Good" at meeting 1 until it reached the maximum score of 40 with the criteria "Very Good" at meeting 3. Student activity at meeting 1 reached 37% with the criteria "A Small Part of Students are Very Active", reached 84% with the criteria "Almost All Students Are Very Active" at meeting 3. Student learning outcomes reached 58% completeness at meeting 1, up to 95% completeness at meeting 3. Based on the results of this research it can be concluded that the SENANG model can improve activities and learning outcomes of students on Mathematics content.